2010
DOI: 10.1049/el.2010.2903
|View full text |Cite
|
Sign up to set email alerts
|

Boost-converter-based solar harvester for low power applications

Abstract: A novel implementation of a solar harvester circuit based on a boost DC/DC converter topology is presented. The proposed circuit is able to harvest solar energy down to a power level of 1.6 mW while maintaining comparable performance with previously presented results at higher power levels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…Besides the experimentally proven ability of the proposed harvester of operating over a large illumination power range, it is also noteworthy to say that the relatively simple topology used for this circuit allowed us to reach harvesting operation down to power levels in the tenths of microwatt range, which to the authors' knowledge has never been demonstrated before for a photovoltaic harvester. Moreover, an efficiency level higher than 60% has been recorded for power level higher than 50 mW and close to 70% for a power level of 1 mW, the latter being among the highest value ever reported in the milliwatt range [5]. …”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Besides the experimentally proven ability of the proposed harvester of operating over a large illumination power range, it is also noteworthy to say that the relatively simple topology used for this circuit allowed us to reach harvesting operation down to power levels in the tenths of microwatt range, which to the authors' knowledge has never been demonstrated before for a photovoltaic harvester. Moreover, an efficiency level higher than 60% has been recorded for power level higher than 50 mW and close to 70% for a power level of 1 mW, the latter being among the highest value ever reported in the milliwatt range [5]. …”
Section: Discussionmentioning
confidence: 63%
“…Various methods have been proposed in order to tune the operation of photovoltaic harvesters, such as the use of the fractional open circuit voltage method [1, 2] and the 'perturb and observe' method [3,4]. However, the efficiency of the proposed systems rapidly drops at low-level illumination and they are practically not able to operate for power levels lower than few milliwatts [4,5].In this Letter, we present a micro-harvesting system based on a frequency-to-voltage MPPT tracker able to operate efficiently also at very low illumination power from a few milliwatts down to few tens of microwatts. The proposed approach consists of the optimisation of circuit efficiency exploiting the change of natural circuit oscillation frequency with illumination power.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lowpower PV panels are generally connected to power processing circuits that have two main blocks: a tracking controller that determines V MPP using diverse methods [1][2][3][4], and a switching DC/DC converter. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the association of such systems with the use of some kind of energy harvesting can reveal an attractive approach, [1]- [6]. Currently, a lot of work is devoted to design efficient small electromechanical devices (microenergy scavengers), that harvest ambient energy and convert it into electricity [1]- [6]. Microenergy scavengers could harvest different types of energy (solar, mechanical, electromagnetic and thermal energy).…”
Section: Introductionmentioning
confidence: 99%